PENGARUH PROMOSI KESEHATAN MELALUI VIDEO ANIMASI TERHADAP TINGKAT PENGETAHUAN DAN SIKAP MENGENAI POLYCYSTIC OVARY SYNDROME (PCOS) PADA REMAJA PUTRI SMA NEGERI XX KOTA BATAM - Nopri Esmiralda; Dhaifina Fajri Amasyitha; Devi Apriani (Universitas Batam, 2026)
ABSTRACT Background: Polycystic ovary syndrome (PCOS) is the most common endocrine disorder in women of reproductive age, with a global prevalence of 3.4–10% and 5–10% in Indonesia. Limited knowledge can delay early detection and increase the risk of complications such as infertility, type 2 diabetes mellitus, and metabolic disorders. Methods: This study used a quantitative pre-experimental one-group pretest–posttest design. An educational video intervention was utilized as a health promotion medium to assess and improve adolescents’ knowledge and attitudes toward PCOS. Data were analyzed using a paired t-test or Wilcoxon Signed Rank Test based on data distribution Results: The Wilcoxon test showed a nilai P of 0.001 for knowledge and 0.001 for attitude, indicating a significant difference before and after the intervention (p < 0.05). Conclusion: Health promotion through animated videos significantly increased knowledge and attitudes about PCOS among female adolescents at SMA Negeri XX in Batam City. Animated videos are effective as a medium for reproductive health education for adolescents Keywords: Polycystic Ovary Syndrome, animated videos, knowledge, attitudes, adolescent girls